1994
DOI: 10.1007/bf02414355
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino method remote measurement of reactor power and power output

Abstract: The question of using neutrino radiation from reactors was first posed in the mid-1970s [1, 2]. The first demonstration measurements were performed when the neutrino laboratory was set up at the Rovno nuclear power plant and it was shown, for a small statistical sample, that neutrino radiation can, in principle, be used in practice [3, 4].The inadequacy of the statistics and the high background of extraneous radiation have always been the main obstacle to recording reactor antineutrinos (~e)' The apparatus pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 1 publication
3
53
0
6
Order By: Relevance
“…where N H is the number of hydrogen atoms in the fiducial volume, R is the distance from the source to the detection point and γ is a constant which takes into account the contributions to the power output made by the fissile isotopes 235 U, 238 U, 239 Pu and 241 Pu [16]. Recent studies have shown the feasibility of using the antineutrino emission from nuclear reactors as an on-line monitor of the reactor activity.…”
Section: The Very Near Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…where N H is the number of hydrogen atoms in the fiducial volume, R is the distance from the source to the detection point and γ is a constant which takes into account the contributions to the power output made by the fissile isotopes 235 U, 238 U, 239 Pu and 241 Pu [16]. Recent studies have shown the feasibility of using the antineutrino emission from nuclear reactors as an on-line monitor of the reactor activity.…”
Section: The Very Near Detectormentioning
confidence: 99%
“…Recent studies have shown the feasibility of using the antineutrino emission from nuclear reactors as an on-line monitor of the reactor activity. A prototype of this kind of detector is running at the San Onofre reactor (U.S.A.) [17], and a previous experiment was done at the Rovno reactor (Ukraine) [16].…”
Section: The Very Near Detectormentioning
confidence: 99%
“…Ainda se considera que a medição do fluxo de neutrinos forneça um espectro da produção de plutônio no núcleo [4].…”
Section: Interação Detector Partículasunclassified
“…No processo de calibração, faz-se necessário se conhecer alguns parâmetros, o que pode ser feito pela espectrometria gama de alguns elementos químicos irradiados no núcleo de um reator de pesquisa [4]. Este é o caso dos detectores de ativação como as folhas de ouro …”
Section: Interação Detector Partículasunclassified
See 1 more Smart Citation